Efeitos do treinamento resistido sobre as alterações na reatividade vascular de ratos diabéticos induzidos por aloxano - Mota, Marcelo Mendonça (2010)
Diabetes mellitus (DM) is presented as a metabolic disorder characterized by chronic hyperglycemia that is associated with endothelial dysfunction (ED). Among the various therapies employed in the improvement of ED, primary prevention, which includes changes in diet and physical training (PT), has been the right one. This study evaluated the effects of resistance training (RT) on vascular reactivity of diabetic rats induced by alloxan. Wistar rats (250-300g) were divided into 3 groups: sedentary control (SC), sedentary diabetic (SD) and diabetic trained with resistance exercise (TD). The TR was performed in a squat aparatus of TAMAKI in 3 sets of 10 repetitions, 3 times a week for 8 weeks. The intensity was set at 40% of the maximum established by the test of one repetition maximum. At the end of the training protocol the animals were sacrificed by exsanguination, and the superior mesenteric artery was removed and sectioned into rings (1-2 mm), which were put into chambers containing 10 mL of Tyrode solution at 37°C and gasified with carbogen. Changes in vascular reactivity to phenylephrine contracturantes agents (PHE) and potassium chloride (KCl) and relaxing, acetylcholine (ACh), sodium nitroprusside (NPS) and pinacidil (PIN) was assessed by obtaining concentration-response curves. It was not observed differences between the potency (pD2) and maximum response (Rmax) of the contractions induced by contract agents in all groups. On the other hand, It was observed a significant (p < 0.05) decrease of Rmax of the relaxation induced by ACh in the SD (79.7 ± 1.4%; n = 6) when compared with SC (98.8 ± 2.0%; n = 6), and an increase in the DT (93.1 ± 2.6%; n = 6), both without changing the pD2. In the presence of L-NAME, the relaxation induced by ACh was significantly (p < 0.05) reduced in SC (from 7.0 ± 0.06 to 5.5 ± 0.1; n = 6) and TD (from 7.0 ± 0.08 to 4.9 ± 0.2; n = 6), but not in SD. Furthermore, it was observed a significant (p < 0.001) increase in the pD2 of SNP in SD (from 7.9 ± 0.08 to 8.3 ± 0.03 compared with SC) and PIN (from 6.2 ± 0.09 to 6.9 ± 0.08 compared with SC). The RT was able to prevent this increase only for PIN (from 6.9 ± 0.08 to 6.3 ± 0.1). These results demonstrate the RT was able to improve the relaxation induced by ACh and to prevent the changes in the sensitivity of the ATP-sensitive potassium channels (KATP) caused by DM. Thus, the RT presents an therapeutic potential in the treatment of vascular complications produced by the DM.